ANALISIS PENGARUH INVESTASI, PDRB, JUMLAH PENDUDUK, PENERIMAAN PEMBANGUNAN, DAN INFLASI TERHADAP PENDAPATAN ASLI DAERAH (PAD) DI KABUPATEN LOMBOK BARAT - Karlina Batik (Jurnal Ekonomi Pembangunan, 2013)
Mark sense application autonomousing to expected region gets to give facility to region to even out its own housewifery, also give room opportunity for region to dig up and mendayagunakan is proprietary potency optimal ala. PAD as one of accepting region reflects to increase region independence. The greater PAD therefore points out that region progressively is able to   dig up and utilizes source those are at its region. To the effect that wants to be reached   in this research is menganalisis affecting investment, PDRB, population, Development acceptance, and inflation to PAD. Observed data in this research is time series's data with runtut time 1980 2007. Estimation model that is utilized is bifilar regression that ditranspormasikan goes to to form logarithm.